Letter to the Editor on Balancing Thromboprophylaxis and Bleeding in Total Joint Arthroplasty: Impact of Eliminating Enoxaparin and Predonation and Implementing Pneumatic Compression and Tranexamic Acid (2016)
We had the opportunity to read last issue’s article by Sharfman et al [1] regarding the use of an intermittent pneumatic compression device (IPCD) and tranexamic acid (TXA) as prophylactic measures against venous thromboembolic disease and bleeding, respectively. The authors’ research on the subject is a valuable contribution to the study of relevant perioperative complications after hip or knee arthroplasty, and their stepwise approach demonstrated interesting results in patient outcomes [1]. Nevertheless, we would like to contribute some observations that could lead to a better understanding of this article, especially regarding its main conclusion. The authors concluded and recommended that using an IPCD and TXA and discontinuing enoxaparin and preoperative autologous blood donation eliminated blood transfusion in hip or knee arthroplasty without any increase in venous thromboembolic disease [1]. However, this could bemisleading due to thelimitations of this study.